Rancang Bangun Exhaust System pada Mobil Minimalis Roda Tiga - Ahyad Bagas Nur Hidayatulloh; Ali Imron; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
One of the three-wheeled vehicles that is currently being developed is a three-wheeled car.In addition to engine selection, in the process of developing a minimalist three-wheeled car will notbe separated from the planning of the exhaust system. In the planning of exhaust system, it isnecessary to calculate the dimensions of the exhaust system pipeline to get the dimensions thatcorrespond to the cylinder capacity of the engine that applied to the minimalist three wheel car. Theapplication of design concept helps design the exhaust system to be able its needed. The designconcept is carried out by identifying plans for laying the driver's seat, ground clearance, and fuellines. The design of the exhaust system is carried out by CFD (Computational Fluid Dynamics) toanalysis the function of the exhaust system by knowing the back pressure that is suitable for theminimalist three wheeled car. Analysis of design concepts can be used as a reference in determiningthe dimensions of the pipe exhaust system which in turn can be a product of the exhaust system for aminimalist three-wheel car.